Arterial hypertension and age at radiation exposure as risk factors of stroke in Chernobyl “liquidators” - I. V. Podsonnaya; G. G. Efremushkin (Кардиоваскулярная терапия и профилактика, 1970)
Aim. To study the role of arterial hypertension (AH) and age at radiation exposure as potential risk factors of stroke (S) in Chernobyl “liquidators”. Material and methods. In total, 109 patients with S in late post-radiation period were examined. By the age at radiation exposure, all participants were divided into 4 groups: Group I (n=5) – under 20 years; Group II (n=61) – 20-29 years; Group III (n=37) – 30-39 years; and Group IV (n=6) – 40-49 years. In each age group, the dynamics of AH and S development was investigated. Results. In patients with AH, comparing to their peers with normal blood pressure, S developed more often, typically in the second decade after the radiation exposure, as a single-episode ischemic event, with neurological symptoms regressing within 24 hours. Maximal S risk was observed in Group II. The risk of haemorrhagic S was highest in Group III patients with AH. Age at radiation exposure was significantly associated with S type, severity, and number. Conclusion. In Chernobyl “liquidators”, AH was linked to increased S incidence. Younger age at radiation exposure was associated with higher risk of developing acute cerebrovascular events earlier in life.